Evaluation of Government Performance and Public Policies in Spain - Feinstein, Osvaldo; ￼￼Zapico-Goni, Eduardo (Washington, DC: World Bank, 2017)
This paper covers selective aspects of Spain's experience in evaluating government performance and public policies. Rather than a cohesive evaluation system, there is instead a constellation of organizations, with evaluation mandates and/or practices, which are not interrelated. These organizations and their respective practices have been evolving without coordination over the past three decades. An evaluation culture is slowly emerging, amid different conceptual approaches used by different organizations that are managing and/or conducting evaluations. Evaluation activity has been taking place in Spain for years, with a marked acceleration and qualitative shift since 2005. Despite Spain's standing as an Organization for Economic Co-operation and Development (OECD) country as well as a European Union (EU) country, it still has not developed a consolidated evaluation system. This fact points out how long-term and complex is the task of institutionalizing an evaluation system. Finally, this paper contains several website addresses where readers can obtain additional information on aspects of the paper that most interest them and to follow the Spanish experience as it unfolds.